Response of the functional traits of Schoenoplectus tabernaemontani to simulated warming in the Napahai wetland of northwestern Yunnan, China - Liu, Zhenya; Zhao, Yiqing; Yu, Hongyan; Zhao, Yao; Guo, Huijun; Sun, Mei (Frontiers in Ecology and Evolution, 2024)
The impact of climate warming on wetland ecosystem is a current focal point in ecological research. This study chose Napahai wetland, a typical plateau wetland in northwest Yunnan province as study site to understand the growth and survival strategies of emergent plants in plateau wetland under climate warming conditions. Using open-top chambers (OTCs) to simulate warming in three treatment (control group、(2.0±0.5) ℃ and (4.0±0.5) ℃ ), studying the response of functional traits of the dominant emergent plant Schoenoplectus tabernaemontani to simulated warming.The results showed that simulated warming significantly reduced the photosynthetic carbon assimilation capacity and biomass accumulation of Schoenoplectus tabernaemontani, and significantly decreased its nitrogen content and vascular bundle density, while significantly increased the vascular bundle size. Growing season accumulated temperature(AT)and the mean of hottest month(WT) were the main temperature factors influencing the functional traits of Schoenoplectus tabernaemontani. In summary, simulated warming significantly affected the functional traits of Schoenoplectus tabernaemontani, demonstrated its effective adaptation to warming conditions. As the temperature rises and the light and productivity decreases, Schoenoplectus tabernaemontani prioritizes the supply of limited resources to the underground part to ensure the biomass supply of the reproductive structure. This study provides a case for revealing the response patterns and ecological adaptation strategies of plateau wetland plants to climate warming.